2012
DOI: 10.1515/hsz-2012-0211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the human tissue kallikrein (KLK) locus and their implication in various malignant and non-malignant diseases

Abstract: Abstract:The Kallikrein ( KLK ) gene locus encodes a family of serine proteases and is the largest contiguous cluster of protease-encoding genes attributed an evolutionary age of 330 million years. The KLK locus has been implicated as a high susceptibility risk loci in numerous cancer studies through the last decade. The KLK3 gene already has established clinical relevance as a biomarker in prostate cancer prognosis through its encoded protein, prostate-specific antigen. Data mined through genome-wide associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 113 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…Basic Local Alignment Search Tool (BLAST) analysis (118) revealed that human kallikrein 12 (h-klk12), a serine protease expressed by adult and fetal tissues (119), share the same VTHPGY sequence that is O -glycosylated in the IIICS domain of human onfFN. It has been well described that h-klk12 modulates many physiological processes (120, 121), as well tumor cell invasion and metastasis (122, 123). Previous studies have shown that cancer cells express kallikreins with atypical glycophenotypes (124).…”
Section: Resultsmentioning
confidence: 99%
“…Basic Local Alignment Search Tool (BLAST) analysis (118) revealed that human kallikrein 12 (h-klk12), a serine protease expressed by adult and fetal tissues (119), share the same VTHPGY sequence that is O -glycosylated in the IIICS domain of human onfFN. It has been well described that h-klk12 modulates many physiological processes (120, 121), as well tumor cell invasion and metastasis (122, 123). Previous studies have shown that cancer cells express kallikreins with atypical glycophenotypes (124).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding KLK3, two SNPs located within the gene and the KLK2-KLK3 intergenic region are strongly associated with CaP patients' survival; also, a functional SNP located at one of the androgen response elements of KLK3 was found to be associated with increased serum PSA levels. Finally, two individual SNPs at KLK3 and KLK15 are strongly related to poorer OC patients' survival (Batra et al 2013;Mavridis et al 2012). …”
Section: Single-nucleotide Polymorphisms (Snps) In the Human Klk Locusmentioning
confidence: 99%
“…More SNVs were noted in KLKs 2, 3, 5, 7, and 13, while fewer were found in KLK9. Compared to prior studies (Goard et al, 2007;Batra et al, 2012), we expanded the number of identified SNVs, as a result of the availability of sequencing information from larger cohorts of individuals. The total number of our identified SNVs is similar to that recently described by Batra et al,who identified 4331 KLK SNVs. Older studies, such as the one by Goard et al, reported on 1856 KLK SNVs in 2007.…”
Section: Snvs At the Human Kallikrein Locusmentioning
confidence: 99%
“…As part of the general extracellular web of proteases, KLK activity is tightly regulated by endogenous inhibitors, activating proteolytic cascades and regulatory feedback that maintain balanced KLK activity . Disruption of this balance and concomitant dysregulation of KLK function has been linked to several diseases, including skin diseases (Eissa and Diamandis, 2008), neurodegenerative diseases, chronic inflammation, diabetes mellitus (Paliouras and Diamandis, 2006;Batra et al, 2012), and cancer (Bharaj et al, 2002;Ahn et al, 2008;Antoniou et al, 2010;Batra et al, 2011). The recent advances in sequencing technologies have brought to light numerous variations, such as single nucleotide variants (SNVs), of several KLK genes, as major contributors to KLK dysregulation in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation